Pilocytic astrocytoma, another way to reach your diagnosis - Rodríguez,Javier Lacorzana (2020)
Abstract Cerebellar astrocytoma (low-grade glioma) is the most frequent tumor of the Central Nervous System in pediatric age, corresponding to 10-20% of brain tumors, having its maximum incidence at 5 years. Brain tumors are the second cause of death at this age, behind leukemias. Its most frequent clinic is headache with vomiting which can worsen in the morning and awaken the patient at night. The most frequent ophthalmological clinic is papilledema and involvement of the cranial nerve VI. In our case we present an atypical presentation (cranial IV), in which a quick derivation favored a better prognosis.